1999
DOI: 10.1088/0953-4075/32/14/305
|View full text |Cite
|
Sign up to set email alerts
|

Merged beam measurement of the dissociative recombination of HCN+and HNC+

Abstract: Cross sections for the dissociative recombination of isomeric HCN+/HNC+ ions with electrons were measured using the single-pass merged beam experiment located at the University of Western Ontario in Canada. The source conditions were varied so that an HCN+/HNC+ mixture was first studied. The HNC+ ion was then isolated via the fast ion-molecule reaction HCN++CO2HNC++CO2. The two sets of measurements, which both refer to vibrationally (and electronically) excited states of HCN+ and HNC+, exhibit differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…[17] Interestingly, for the first time, the differences between the direct and indirect processes (HCN + /HNC + isomers) have now been observed experimentally [Sheehan et al, 1999;Talbi et al, 2000]. The direct process has been found to be the considerably more efficient of the two, with a rate coefficient nearly 30 times larger than that for the indirect process in this instance.…”
Section: An Overview Of the Dissociative Recombination Processmentioning
confidence: 85%
“…[17] Interestingly, for the first time, the differences between the direct and indirect processes (HCN + /HNC + isomers) have now been observed experimentally [Sheehan et al, 1999;Talbi et al, 2000]. The direct process has been found to be the considerably more efficient of the two, with a rate coefficient nearly 30 times larger than that for the indirect process in this instance.…”
Section: An Overview Of the Dissociative Recombination Processmentioning
confidence: 85%
“…It was also observed that the products of dissociation lead to extensive fragmentation of the ion. The dissociative recombination reactions of HCN þ and HCNH þ have also been examined using a single pass merged beam method (Sheehan et al, 1999) and for HCNH þ the storage ring method was also used (Semaniak et al, 2001). HCN and HNC were found to make up 67% of all recombination products from recombination of HCNH þ .…”
Section: Summary Of Known Ion Chemistry Pertaining To Titanmentioning
confidence: 99%
“…The process of dissociative recombination is an important process in which the electron is captured by a molecular ion resulting in a number of neutral products. It is an efficient process producing complex neutral molecules: H^ (Larson et al 2000, Serov et al 2001, Pichl, Nakamura, k Horacek 2001, HD+ (Amitay et al 1999, Larson et al 2000, Orel 2000, Larson k Orel 2001, IL+ (Jensen et al 2001, Glosfk et al 2001, Strasser et al 2001a, H 2 0+ (Jensen et al 1999), H 3 0+ (Neau et al 2000, Bahati et al 2001c), HCN+ (Sheehan et al 1999, Talbi, LePadellec, k Mitchell 2000, HeJ (Carata, Orel, k Suzor-Weiner 1999), HeH+ (Larson k Orel 1999), LiH+ (Krohn et al 2001), CH+ (Carata et al 2000), C2H+ (Derkatch et al 1999), OH+ (Larson et al 2000), O j (Peverall et al 2001), and NO+ (Mostefaoui et al 1999, Schneider et al 2000, LePadellec et al 2001.…”
Section: Electron Impact Of Moleculesmentioning
confidence: 99%